Acidentes com tratores agrícolas e a interrupção de um projeto de vida: a construção da cultura da prevenção - Guinot, Karen de Oliveira (2019)
The following study proves itself once it approaches matters involving labor accidents in rural activities, their causes and consequences, specially the accidents related to agricultural machines. In this context it is relevant to work on the matter that embraces the field of prevention, since, in order to enable the decrease of effective incidence of such accidents its important, first, to work the prevention culture as a way to minimize or erradicate inferent risk to the accidents. Therein this work aimed at surveying cases which involved labor accidents according to previously defined methodological criteria on the occasion of the thesis project qualification. The original planned hypothesis for the study was thougt to reinforce awareness of the prevention cultural wich will cause, as a logical via of consequence, a decrease in risk and labor accident occurance with agricultural machines (tractors) in RGS, from the results obtained to define which attitudes should be adopted by managers and rural workers to change the accident scenario in the RGS, since it is impracticable to talk about reducing the number of accidents without prioritizing a prevention culture. This way, a previous diagnosel of the most common accidents was done, regarding the State of RGS and Brazil. In this sense, data were collected from the Social Security Agency involving occupational accidents in Brazil and the RGS, to assess whether their incidence has increased or decreased over the last decade. Also, through the same institution and through date gathering it was possible to draw a profile of the most vulnerable workers, considering workers gender and age, as well as the consequences generated by the accidents. In addition, as a distinguishing study feature a sixty judicial case survey was carried out. They included accidents with farm machines in the State of Rio Grande do Sul, from 2000 to 2018, aiming at examining the phatic peculiarity of accidents, specially based on the judicial inspection, in which it is possible to specify behaviors and check if preventive measures were or were not followed by employees and employers. Nevertheless, at the survey accomplished in the lawsuits, it was possible to find out about accident typologies, the consequences to workers, responsibility and workers’ capability to work or not, as well as deaths.